Is there a hearing aid for the thinking person? - Hafter ER (Journal of the American Academy of Audiology, 2010)
Background: The history of auditory prosthesis has generally concentrated on bottom-up processing, that is, on audibility. However, a growing interest in top-down processing has focused on correlations between success with a hearing aid and such higher order processing as the patient's intelligence, problem solving and language skills, and the perceived effort of day-to-day listening. Purpose: Examination of two cases of cognitive effects in hearing that illustrate less-often-studied issues: (1) Individual subjects in a study use different listening strategies, a fact that, if not known to the experimenter, can lead to errors in interpretation; (2) A measure of shared attention can point to otherwise unknown functional effects of an algorithm used in hearing aids. Research design: In the two examples described above: (1) Patients with cochlear implants served in a study of the binaural precedence effect, that is, echo suppression. (2) Individuals identifying speech-innoise benefit from noise reduction (NR) when the criterion was improved performance in simultaneous tests of verbal memory or visual reaction times. Conclusions: Studies of hearing impairment, either in the laboratory or in a fitting session, should includestudy of the complex stimuli that make up the natural environment, conditions where the thinking auditory brain adopts strategies for dealing with large amounts of input data. In addition to well-known factors that must be included in communication, such things as familiarity, syntax, and semantics, the work here shows that strategic listening can affect even how we deal with seemingly simpler requirements, localizing sounds in a reverberant auditory scene and listening for speech in noise when busy with other cognitive tasks.